Multiple intracranial aneurysms followed left atrial myxoma: case report and literature review - Xu, Qingsheng (Pioneer Bioscience Publishing Company, 2013)
Cerebral aneurysms follows atrial myxoma is a rare neurological complication. We report a patient with multiple cerebral aneurysms three years after resection of left atrial myxoma and further review the literature. The characteristics of these aneurysms are indefinite and variable. They can occur prior or post the resection of cardiac myxoma. “Metastasize and Infiltrate” theory may be the key mechanism in the formation of these aneurysms. Magnetic resonance imaging (MRI), computed tomography (CT) and angiography are useful in the diagnosis while digital subtraction angiography (DSA) is the best choice. There are no definite guidelines for therapy of these aneurysms. Resection of the cardiac myxomas, chemotherapy, radiotherapy, coil embolization and surgical treatment could be helpful.